Estimating the effects hydro climatic variability and its extreme events have on economic growth of Kenya - Wainaina, Jessica (Strathmore University, 2021)
The cunent effect of climate change on economic growth needs to be understood. Climate change has affected the hydro climatic system and thus rising temperatures and unpredictable rainfall have led to hydroclimatic variability. Due to this, extreme weather events such as floods, droughts and heavy storms have increased in frequency and intensity. This study seeks to investigate the effects ofhydroclimatic variability on the economic growth ofKenya and detennine which hydroclimatic extreme event has a substantial effect on the economic growth of Kenya. A time series analysis covering the years 1965 to 2019 is canied out with the Mankiw-Weil-Romer growth model based on the Neoclassical growth theory. We see the effects climate variables: temperature and rainfall variability have on GDP growth rate while also including other variables that affect growth namely gross fixed capital, population and human capital. To capture the extreme events namely drought and floods in the model, a precipitation index called Weighted Anomaly Standardized Precipitation (WASP) index is applied. From analysis ofhydroclimatic variability, we establish that change in temperature has a positive effect on economic growth both in short run and long run. Severe droughts are the most occuning extreme event followed by the severe floods. Drought effects have a higher magnitude of effect on GDP growth rate compared to floods. Moderate drought has a slightly higher effect on GDP growth rate but the magnitude of severe drought is still very high. Severe drought still has a negative effect on the economy growth in the long run and is thus worth looking into solving this issue.
Submitted in partial fidfiJJment of the requirements for the Degree of Bachelor of Business Science in Financial Economics at Strathmore University